Changes of Functional Recovery of Ankle Joint with Application of Rehabilitation Exercise Program after Arthroscopic Modified Brostrom Operation: A Pilot Study - Ji Myeong Park; Ho Jin Kim; Se Hee Kong (Asian Society of Kinesiology, 2021)
OBJECTIVES The purpose of this study was to demonstrate its effectiveness by applying a systematic rehabilitation exercise program to patients after arthroscopic modified Brostrom operation. METHODS The research subjects were 13 patients who had arthroscopic modified Brostrom operation, the 60-minute rehabilitation exercise program was applied twice a week for six weeks, and then, subjective evaluation of ankle joint, and its dynamic stability and isokinetic muscle strength were measured. RESULTS After application of the rehabilitation exercise program, subjective evaluation of the ankle joint(p<.001), its dynamic stability(p<.001) and strengths of the involved side for isokinetic muscle strength peak torque inversion(p<.001), eversion(p<.01), total work inversion(p<.001), eversion(p<.01) uninvolved side peak torque inversion(p<.001), eversion(p<.01), total work(p<.01), muscle endurance of the involved side peak torque inversion(p<.001), eversion(p<.01), total work inversion(p<.001), eversion(p<.01), uninvolved side peak torque inversion(p<.01), total work inversion(p<.01) were significantly increased. CONCLUSIONS It was confirmed that application of rehabilitation exercise program after arthroscopic modified Brostrom operation was effective for positive possibilities of its settlement as regular rehabilitation exercise program.